A Research Article Phytochemical and Pharmacological Evaluation of Carthamus tinctorius Leaves - Pant, Rahul; Irchhaiya, Raghuveer; Rao, Ch. V. (Journal of Drug Delivery and Therapeutics, 2019)
Hepatoprotective activity of methanolic extract of leaves of Carthmus tinctorius L. (MECT) was investigated against hepatotoxicity produced by administering a combination of two anti-tubercular drugs Isoniazid and Rifampicin for 24 days by Oral route in rats. MECT were administered at two graded dose i.e. 200 and 300 mg/kg p.o. 45 min after to anti-tubercular challenge for 24 days. MECT was evident in the all doses as there was a significant decrease in AST, ALT, ALP, and Total Bilirubin levels. MECT significantly decreased the level of these biochemical parameter as compared to control. HPTLC analysis showed the presence of B-sitosterol and Lupeol in MECT. Results showed that Carthamus tinctorius possess significant Hepatoprotective activity which might be due to flavonoids.Keywords: Carthamus tinctorius leaves1, hepatoprotective2, Rifampicin3, Isoniazide4, SGPT5.